2008
DOI: 10.1186/1476-9255-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory role of amphiregulin, an epidermal growth factor family member whose expression is augmented in rheumatoid arthritis patients

Abstract: Background: The epidermal growth factor (EGF) and EGF receptor (EGFR) families play important roles in the hyperplastic growth of several tissues as well as tumor growth. Since synovial hyperplasia in rheumatoid arthritis (RA) resembles a tumor, involvement of the EGF/EGFR families in RA pathology has been implied. Although several reports have suggested that ErbB2 is the most important member of the EGFR family for the synovitis in RA, it remains unclear which members of the EGF family are involved. To clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 42 publications
(41 reference statements)
3
73
1
2
Order By: Relevance
“…These transmembrane proteins bind polypeptide ligands, mainly growth factors. Among the 58 RTK family members, epidermal growth factor receptor, plateletderived growth factor (PDGF) receptor (PDGFR), fibroblast growth factor receptor, vascular endothelial growth factor receptor, hepatocyte growth factor receptor (c-Met), and stem cell growth factor receptor (c-kit) have been shown to be expressed in rheumatoid synovial tissues (11)(12)(13)(14)(15)(16)(17)(18)(19). On the basis of their roles as growth factor receptors, several RTKs are the driving force for onset or progression of various diseases such as malignancy and arthritis and may represent key targets in therapeutic treatments.…”
mentioning
confidence: 99%
“…These transmembrane proteins bind polypeptide ligands, mainly growth factors. Among the 58 RTK family members, epidermal growth factor receptor, plateletderived growth factor (PDGF) receptor (PDGFR), fibroblast growth factor receptor, vascular endothelial growth factor receptor, hepatocyte growth factor receptor (c-Met), and stem cell growth factor receptor (c-kit) have been shown to be expressed in rheumatoid synovial tissues (11)(12)(13)(14)(15)(16)(17)(18)(19). On the basis of their roles as growth factor receptors, several RTKs are the driving force for onset or progression of various diseases such as malignancy and arthritis and may represent key targets in therapeutic treatments.…”
mentioning
confidence: 99%
“…Other investigators reported that AREG overexpression is followed by the production of several proinflammatory cytokines [20][21][22][40][41][42] in autoimmune disorder. EGFR inhibition decreased the protein expression of IL-6 by adipose tissue macrophages, reducing the proinflammatory state, 22 and TNF-a stimulates airway smooth muscle cells to express many proinflammatory mediators such as IL-6, chemokines, growth factors and adhesion molecules known to be involved in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Our present hypothesis explores first, whether anti-Ro/SSA Abs-mediated TACE activation is responsible for AREG activation. As recent studies have demonstrated that AREG could induce proinflammatory cytokines secretion in epithelial cells, [20][21][22] as second step, we discuss how TACEmediated AREG shedding, caused by anti-Ro/SSA Abs treatment, could have a critical role in TNF-a-induced IL-6 and IL-8 secretion by SGEC. Finally, we evaluate the effect of adalimumab and gene silencing on AREG expression and on TNF-a-AREG-mediated proinflammatory IL-6 and IL-8 secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relative mRNA levels were calculated with the ΔΔCt method using glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA as an internal control. The primers used in this study are as follows: 5'-GTGGTG CTGTCGCTCTTGATACTC-3' and 5'-TCAAATCCATCAGCACT GTGGTC-3' for AREG (13), and 5'-GCACCGTCAAGGCTG AGAAC-3' and 5'-ATGGTGGTGAAGACGCCAGT-3' for GAPDH (11). The experiments were performed in triplicate.…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%